2016
DOI: 10.1177/0037549716656791
|View full text |Cite
|
Sign up to set email alerts
|

Model-based testing methodology using system entity structures for MATLAB/Simulink models

Abstract: The increasing complexity of systems entails an increasing complexity of simulation models. Likewise, heterogeneity in system components corresponds to heterogeneous simulation models. Cyber physical systems (CPS) represent an emerging class of technical systems characterized by their complexity and heterogeneity. Developing simulation models for CPS brings various challenges, one of which is determining the simulation fidelity. Fidelity evaluation can be introduced as the degree to which a simulation model ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…These experimental frames (EF) helped documenting the meta-information necessary to execute the model itself. Traore and Mazy [21] formalized this EF concept and Schmidt et al [20] showed the use of EFs within the model-based testing of simulation models. Denil et al [5] observed that a modelâĂŹs frame depends on the activity that is performed and describes why different activities require different frames.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These experimental frames (EF) helped documenting the meta-information necessary to execute the model itself. Traore and Mazy [21] formalized this EF concept and Schmidt et al [20] showed the use of EFs within the model-based testing of simulation models. Denil et al [5] observed that a modelâĂŹs frame depends on the activity that is performed and describes why different activities require different frames.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Simulation Function of Matlab. As one of the core components of Matlab, the Simulink module [9,10], from its main function, creates a dynamic system modeling, integrated numerical analysis, and simulation integrated environment. Because it works under the Windows interface, there is no need to write large numbers of programs, so that the editing interface and the block diagram of the control system are very convenient.…”
Section: Simulation and Application Example Of Matlabmentioning
confidence: 99%
“…(Spiegel et al 2005) document the non-trivial challenge of re-using EFs due to the complexity of their constraints. Recently (Schmidt et al 2016) showed how they use EFs for model-based testing of MATLAB/Simulink models.…”
Section: Related Workmentioning
confidence: 99%